2001
DOI: 10.1093/oxfordjournals.molbev.a003959
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Amplifications and Deletions of Satellite DNA Accompanied Chromosomal Diversification in South American Tuco-tucos (Genus Ctenomys, Rodentia: Octodontidae): A Phylogenetic Approach

Abstract: We investigated the relationship between satellite copy number and chromosomal evolution in tuco-tucos (genus Ctenomys), a karyotypically diverse clade of rodents. To explore phylogenetic relationships among 23 species and 5 undescribed forms, we sequenced the complete mitochondrial cytochrome b genes of 27 specimens and incorporated 27 previously published sequences. We then used quantitative dot-blot techniques to assess changes in the copy number of the major Ctenomys satellite DNA (satDNA), named RPCS. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 49 publications
9
84
2
3
Order By: Relevance
“…This supports the suggestion of D 'Elía et al (1999) and Slamovits et al (2001) that the asymmetric morph appeared more than once in the evolutionary history of Ctenomys. The uncertain position of C. maulinus, a species with the asymmetric sperm, and the lack of sequence data for C. yolandae, which has a third sperm morphology (Vitullo et al 1988), hinders the recovery of the evolutionary history of this variable trait.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This supports the suggestion of D 'Elía et al (1999) and Slamovits et al (2001) that the asymmetric morph appeared more than once in the evolutionary history of Ctenomys. The uncertain position of C. maulinus, a species with the asymmetric sperm, and the lack of sequence data for C. yolandae, which has a third sperm morphology (Vitullo et al 1988), hinders the recovery of the evolutionary history of this variable trait.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, Cook and Yates (1994) studied allozymic variation for Bolivian species, and Ortells (1995) examined the variation of karyotype G-band patterns in Argentinean species. More recently, Lessa and Cook (1998), D'Elía et al (1999), Mascheretti et al (2000), and Slamovits et al (2001) analyzed sequences of the mitochondrial cytochrome-b gene of some Argentinian, Brazilian, Bolivian, Chilean, and Uruguayan species (Table 1). Most of these arrangements were given additional support by phylogenetic reconstructions on the basis of sequences of 2 nuclear introns (Castillo et al 2005).…”
mentioning
confidence: 99%
“…We must therefore envisage that the amplification of other repetitive sequences in heterochromatin or euchromatin may be associated in one way or another with the TE copy number on chromosome arms. For example, in plants it is the size of repetitive blocks between genes that correlates with genome size (Chen et al 1997), and amplification and deletion of satellite DNA has been observed in many species (Csink and Henikoff 1998;Slamovits et al 2001), all phenomena which could have involved chromatin remodeling (Henikoff, Ahmad, and Malik 2001). The fact that D. simulans males have bigger genomes than females may indicate a specific increase of repeated sequences in the heterochromatin of the Y chromosome of that species.…”
Section: Discussionmentioning
confidence: 99%
“…У этого вида описана система тревожной сигнализа-ции в ответ на проникновение хищников (Pearson, Christie, 1985;Lacey et al, 1997;Lacey, Wieczorek, 2004). Такой образ жизни ведет к сильной генетической и простран-ственной структурированности популяций тукотуко, значительной внутри и межвидовой дивергенции за счет дрейфа генов Lessa, Cook, 1998;Lessa, 2000;Slamovits et al, 2001;Mora et al, 2006).…”
Section: распространение и образ жизни рода Ctenomysunclassified